Enzyme-Assisted Fucoidan Extraction from Brown Macroalgae Fucus distichus subsp. evanescens and Saccharina latissima - Thuan Thi Nguyen; Maria Dalgaard Mikkelsen; Vy Ha Nguyen Tran; Vo Thi Dieu Trang; Nanna Rhein-Knudsen; Jesper Holck; Anton B. Rasin; Hang Thi Thuy Cao; Tran Thi Thanh Van; Anne S. Meyer (Marine Drugs, 2020)
Fucoidans from brown macroalgae (brown seaweeds) have different structures and many interesting bioactivities. Fucoidans are classically extracted from brown seaweeds by hot acidic extraction. Here, we report a new targeted enzyme-assisted methodology for fucoidan extraction from brown seaweeds. This enzyme-assisted extraction protocol involves a one-step combined use of a commercial cellulase preparation (Cellic®CTec2) and an alginate lyase from Sphingomonas sp. (SALy), reaction at pH 6.0, 40 °C, removal of non-fucoidan polysaccharides by Ca2+ precipitation, and ethanol-precipitation of crude fucoidan. The workability of this method is demonstrated for fucoidan extraction from Fucus distichus subsp. evanescens (basionym Fucus evanescens) and Saccharina latissima as compared with mild acidic extraction. The crude fucoidans resulting directly from the enzyme-assisted method contained considerable amounts of low molecular weight alginate, but this residual alginate was effectively removed by an additional ion-exchange chromatographic step to yield pure fucoidans (as confirmed by 1H NMR). The fucoidan yields that were obtained by the enzymatic method were comparable to the chemically extracted yields for both F. evanescens and S. latissima, but the molecular sizes of the fucoidans were significantly larger with enzyme-assisted extraction. The molecular weight distribution of the fucoidan fractions was 400 to 800 kDa for F. evanescens and 300 to 800 kDa for S. latissima, whereas the molecular weights of the corresponding chemically extracted fucoidans from these seaweeds were 10–100 kDa and 50–100 kDa, respectively. Enzyme-assisted extraction represents a new gentle strategy for fucoidan extraction and it provides new opportunities for obtaining high yields of native fucoidan structures from brown macroalgae.